Relevansi Prinsip Demokrasi dalam Praktik Pengangkatan Menteri dari Pimpinan Partai Politik pada Sistem Presidensial (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
The main issue in this study is the practice of ministers concurrently holding positions as party chairpersons, despite conflicting with the provisions of Article 23 of Law No. 39 of 2008 concerning State Ministries, which prohibits ministers from concurrently serving as leaders of organizations funded by the state budget (APBN/APBD), including political parties that receive APBN/APBD funds. The focus of this research is on the reasons why the president appoints ministers from political party leadership and the implications of such dual positions. The method used is normative legal research with statutory and conceptual approaches, and data collection through literature review of regulations, literature, and other official documents. The study reveals that the main factors behind appointing ministers from party leadership are the dynamics of the multiparty system requiring the president to rely on coalition support, regulatory ambiguity regarding the prohibition of dual office holding, and political pragmatism that undermines the party’s role as representatives of the people. The implications of this practice include violations of Law No. 39 of 2008, weakening of checks and balances mechanisms, potential for transactional politics, strengthening of oligarchy and political dynasties, and violation of good governance principles. To address these issues, a revision of Article 23 of Law No. 39 of 2008 is necessary to make the prohibition of dual offices clearer, strengthen law enforcement mechanisms, ensure transparency in ministerial appointments, and secure the president’s commitment to meritocratic principles.